160 Gbit/s Field Transmission over 116 km Standard Single Mode Fiber Using 160 Gbit/s OTDM and 40 Gbit/s ETDM Demultiplexer - Feiste, U.; Ludwig, R.; Schubert, C.; Berger, J.; Schmidt, C.; Weber, H. G.; Rumpf, F.; Schmauß, Bernhard; et al. (IEE Proceedings Optoelectronics, 2001)
T. Systems Nova, Technologiezentrum, the first 160 Gbit/s RZ transmission experiment over field-installed standard fibre G.652 is reported. The transmitter rests upon the OTDM technique. At the receiver, a 160 Gbit/s to 40 Gbit/s OTDM demultiplexer followed by 40 Gbit/s electrical signal processing (ETDM) is used. The results are compared with 160 Gbit/s to 10 Gbit/s OTDM demultiplexing experiments. The OTDM demultiplexer is based on cross phase modulation in a semiconductor optical amplifier.
UnivIS-Import:2015-03-09:Pub.2001.tech.IE.LEH.160gbi_1